The interface of disasters, sanitation, and poverty in Brazil: a sociological perspective - Valencio, Norma; Valencio, Arthur; Baptista, Murilo S. (Frontiers in Sustainable Cities, 2023)
In Brazil, the high frequency and types of disasters are symptoms of misguided socioenvironmental public policies. While approximately 25% of municipalities decree emergency every year, over 75% of the occurrences are linked to sanitation issues. Such events range from the lack of urban drainage infrastructure to handle large volumes of rainwater to the insufficiency of backup water supply strategies during prolonged drought, both further impacting other precarious infrasystems such as solid waste management and sewage, with the most heavily and extensively affected group being the citizens facing poverty. Therefore, the issues of disaster, sanitation, and poverty are intertwined in Brazil. Using a network science approach, we investigate how the sociological debate is overcoming the fragmented approach about these subthemes and within the disciplinary fields in social sciences by analyzing the connections between the keywords of the open-access research articles from 2003 to 2022 from four databases. This mini review highlights the main contemporary axes between the themes, identifies the potential for tackling the gap at the interface, and clarifies the needs for future studies given the aims of the Sustainable Development Goals.